2011
DOI: 10.1111/j.1600-0765.2011.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich fibrin and bovine porous bone mineral vs. platelet‐rich fibrin in the treatment of intrabony periodontal defects

Abstract: Lekovic V, Milinkovic I, Aleksic Z, Jankovic S, Stankovic P, Kenney EB, Camargo PM. Platelet‐rich fibrin and bovine porous bone mineral vs. platelet‐rich fibrin in the treatment of intrabony periodontal defects. J Periodont Res 2012; 47: 409–417. © 2011 John Wiley & Sons A/S Background and Objective:  Bovine porous bone mineral (BPBM) is a xenograft that has been successfully utilized in periodontal regeneration. Platelet‐rich fibrin (PRF) is a leukocyte and platelet preparation that concentrates various polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
144
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(159 citation statements)
references
References 35 publications
5
144
0
10
Order By: Relevance
“…Comparing with an arm of the study conducted by Pradeep AR et al, in which a combination of PRF and porous hydroxyapatite were used with OFD in mandibular Class II furcation defects [11], the mean reduction in PPD was 3.68±1.07 mm and mean relative vertical clinical attachment gain was 3.31±0.52 mm both being in accordance with the results of this study. In a study by Lekovic V et al, wherein the investigators combined bovine porous bone mineral and PRF and by Pradeep AR et al, wherein porous hydroxyapatite was combined with PRF in the management of intrabony defect a significant reduction in PPD and gain in clinical attachment level was observed from baseline [12,13]. This is in accordance with the results of this study though a direct comparison is debatable since defect morphology can influence the outcome of regenerative procedures.…”
Section: Resultssupporting
confidence: 80%
“…Comparing with an arm of the study conducted by Pradeep AR et al, in which a combination of PRF and porous hydroxyapatite were used with OFD in mandibular Class II furcation defects [11], the mean reduction in PPD was 3.68±1.07 mm and mean relative vertical clinical attachment gain was 3.31±0.52 mm both being in accordance with the results of this study. In a study by Lekovic V et al, wherein the investigators combined bovine porous bone mineral and PRF and by Pradeep AR et al, wherein porous hydroxyapatite was combined with PRF in the management of intrabony defect a significant reduction in PPD and gain in clinical attachment level was observed from baseline [12,13]. This is in accordance with the results of this study though a direct comparison is debatable since defect morphology can influence the outcome of regenerative procedures.…”
Section: Resultssupporting
confidence: 80%
“…8,9 PRF has been used in different surgical procedures such as sinus floor augmentation, treatment of gingival recession (GR), furcation defects, maxillary rehabilitation before implant placement, restoration of peri-implant defects, as well as healing of extraction sockets with promising results. 10,11,12,13,14 In addition, certain clinical studies have been conducted on the use of PRF for treatment of intra-bony defects in humans, 15,16,17,18,19 but none have investigated its additive effects with ABBM for treatment of intra-bony defects. Thus, the present split-mouth, single-centre, controlled study aimed to compare the healing of intra-bony defects treated with a combination of ABBM-PRF or ABBM alone; the hypothesis being tested was that PRF would augment the regenerative effects of ABBM in human intra-bony defects.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in concordance with those of the aforementioned studies. 36,37 Several studies 15,16,17,38 have examined the suitability of autologous PRF for treatment of human intra-bony defects and revealed that PRF improves clinical 15 and radiographical 15,16,17,38 parameters. However, in the present study, no statistically significant differences were observed between both groups, except for the significant CAL gain noted in the test group.…”
mentioning
confidence: 99%
“…9,10 Likewise, the efficiency of PRF was also proved when used in conjunction with other type of bone graft materials. 11 But, studies or reports combining both PRF and hydroxy apatite crystals are lacking. Since, hydroxy apatite is easily available and also cost effective; we used hydroxy apatite crystals in our study.…”
Section: Discussionmentioning
confidence: 99%